Transformasi Bunyi Aktivitas Rumah Tangga Menjadi Ekspresi Artistik dalam Karya “Bisikan Cucian” - Maharani, Septi Putri; Apriani, Arni; Setiaji, Deden (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study explores the creation process of a contemporary music composition entitled “Bisikan Cucian” (“The Whisper of Laundry”), which originates from the sonic exploration of domestic activities, particularly manual laundry routines. Through an experimental and reflective approach, this work transforms everyday household sounds such as water splashes, fabric friction, whispers, and hanger taps into the main elements of its musical structure. The study adopts a qualitative method with an artistic research approach, involving direct observation, sound recording, selection, and composition based on expressive and narrative values. The composition aims to reframe domestic labor as a legitimate artistic space, while presenting emotional narratives and personal reflection through sound and bodily movement. In addition to voicing personal experiences, “Bisikan Cucian” addresses gender issues and body aesthetics, challenging conventional listening spaces by highlighting often-ignored sounds. The result reveals that domestic soundscapes hold strong artistic potential when consciously and contextually processed, and that they can expand the discourse of contemporary sound art in Indonesia through the lens of everyday aesthetics and acoustic ecology.